Educação ambiental nos currículos e na prática pedagógica da Escola Cidadã Integral Técnica (Ecit): análise dos cursos técnicos no Vale do Mamanguape (Pb) - Cesar, Ary Gustavo da Silva (2024)
The National Environmental Education Policy (PNEA) provides for a multidisciplinary, continuous, and integrated approach to regional differences and national interests. According to the National Common Curricular Base for secondary education, the environment is a transversal theme. However, reports of specific and isolated pedagogical practices persist in the literature. Since 2018, the state of Paraiba has started to offer middle school technical education through a model called Escola Cidadã Integral and Escola Cidadã Integral Técnica (ECI/ECIT), which advocates education supported by human values and with principles focused on citizenship, converging with the politics of equality, ethics, and identity, with respect for differences. The research carried out in this dissertation aimed to analyze the environmental theme in the syllabi and pedagogical practice of the ECIT, middle school technical education, at Vale do Mamanguape (north coast of Paraiba), an Indigenous territory rich in socio-environmental diversity. We carried out a qualitative investigation of an exploratory nature, using bibliographical research, document analysis, and data collection through a questionnaire applied to teachers from two ECITs, delimiting the study to a technical course in each school, one in Agribusiness, the other in Agroecology. Environmental Education is not included in the Paraíba Comprehensive Education Program. In the other documents analyzed, there are no guidelines for its implementation and no guidance for including the subject in the ECIT curriculum. The questionnaires revealed that the teachers have a satisfactory understanding of the concept of the environment and recognize its relationship with education in a dialogical and interdependent way. Still, they perceive it in a reductionist way. Amid this, among them, the prevailing conception of environmental education is a naturalistic environment in which the environment is seen as something natural and untouchable, with a cognitive focus, summarized as the mere transmission of knowledge about nature. Despite this, given the environmental themes proposed to teachers, we would point out that they can be worked on in various other subjects in the school curriculum, as well as in other specific features of the ECIT model, such as themed classrooms, protagonism clubs, entrepreneurial subjects, elective subjects, daily reception, experimental practices, course completion work and life projects, thus creating a continuous and permanent process of environmental education. The data collected and analyzed in the study above showed a situation that, while considering the significant advances in the inclusion of environmental issues in schools, even if they perceive the environmental dimension as part of education, placing it in a transversal and interdisciplinary way environmental education has been implemented within the scope of curricular discussions, even if it does not receive the treatment expected from a critical, political and emancipatory environmental education.